The exercise is lớn evaluate it. In my text book the answer is \$0\$I tried to factor the expression, but it got me nowhere.

Bạn đang xem: S

\$\$sin^4 x+cos^4 x=(sin^2 x+cos^2 x)^2-2sin^2xcos^2x=1-2sin^2xcos^2x\$\$\$\$sin^6 x+cos^6 x=(sin^2 x+cos^2 x)^3-3sin^2 xcos^2 x(sin^2 x+cos^2 x)=1-3sin^2xcos^2x\$\$

\$\$2-6sin^2xcos^2x-3+6sin^2xcos^2x+1\$\$

Which is \$0\$, for all \$x\$.

\$\$2(sin^6x +cos^6x) - 3(sin^4x+cos^4x)+1=\$\$\$\$=2(sin^2x +cos^2x)(sin^4x-sin^2x cos^2 x+cos^4x) - 3(sin^4x+cos^4x)+1=\$\$\$\$=2(sin^4x-sin^2x cos^2 x+cos^4x) - 3(sin^4x+cos^4x)+1=\$\$\$\$=-2sin^2x cos^2 x -sin^4x-cos^4x+1=\$\$\$\$-(sin^2x +cos^2x)^2+1=-1+1=0\$\$

\$\$eginalign1&=left(sin^2(x)+cos^2(x) ight)^3\&=sin^6(x)+3sin^4(x)cos^2(x)+3sin^2(x)cos^4(x)+cos^6(x)\&=sin^6(x)+3sin^2(x)cos^2(x)+cos^6(x) ag1\\1&=left(sin^2(x)+cos^2(x) ight)^2\&=sin^4(x)+2sin^2(x)cos^2(x)+cos^4(x) ag2endalign\$\$Subtracting \$3\$ times \$(2)\$ from \$2\$ times \$(1)\$ gives \$-1\$. Therefore,\$\$2left(sin^6(x)+cos^6(x) ight)-3left(sin^4(x)+cos^4(x) ight)+1=0 ag3\$\$

Consider \$a^3+b^3=(a+b)^3-3ab(a+b)\$ and \$a^2+b^2=(a+b)^2-2ab\$. For \$a=sin^2x\$ & \$b=cos^2x\$ we have\$\$2(sin^6x+cos^6x)-3(sin^4x+cos^4x)+1=2(a+b)^3-6ab(a+b)-3(a+b)^2+6ab+1\$\$However, \$a+b=sin^2x+cos^2x=1\$, so the expression simplifies to\$\$2-6ab-3+6ab+1=0\$\$

## Not the answer you're looking for? Browse other questions tagged algebra-precalculus trigonometry or ask your own question.

\$int_-pi/2^pi/2 fracsin^2012xleft(1+ alpha^x ight)left(sin^2012 x+cos^2012x ight);dx \$
How to simplify \$fracsqrt2+2(cos 20^circ+cos 25^circ)sin left(90-frac452 ight)sin 55^circ sin 57.5^circ\$?

Xem thêm: Tính Ph Dung Dịch Hcl 0 01M Có Ph Bằng 2, Tính Ph Dung Dịch X Gồm Hcl 0,01M Và H2So4 0,02M

Site design / hình ảnh sản phẩm © 2022 Stack Exchange Inc; user contributions licensed under cc by-sa. Rev2022.4.21.42004